Categorizing Communication Errors in Integrated Hospital Information Systems - Saboor, S.; Ammenwerth, E. (Methods of Information in Medicine, 2009)
Objectives: Hospital information systems (HIS) are the hospital’s nervous system. The HIS are mostly grown over several years, dedicated to specific needs and comprise individual workarounds. Changes to such complex systems may cause a variety of different negative side-effects. In order to understand the nature of incorrect communication in integrated HIS, a concise structured categorization of common communication problems and their reasons is essential. The objective of this paper is to present such a categorization, its development and verification.Methods: We used a combined approach for the development of the error categorization: We started with a qualitative content analysis on available literature in PubMed. In order to ensure the validity and completeness of the results, we chose the method of problem-centered expert interviews.Results: The resulting categorization of communication problems is represented as a five-level hierarchy. It comprises 81 problems that are related to the electronic communication. Further, it contains in total 229 entries that are either the reasons of these problems or recommendation for avoiding the problems.Conclusion: To our knowledge there is no similar summary that concisely summarizes common communication problems and also refers to their underlying reasons. Equivalent content is mostly published in experience reports that just concentrate on single aspects. We used the details of such references in order to compile our categorization – it thus can be regarded as an intersection of relevant experiences. The categorization can raise a basic awareness on potential problems and supports the understanding of the underlying reasons. An evaluation in a real environment must prove whether the content of the categorization is correct.
Keywords: Classification; HIS management; systems architecture; information system